2017
DOI: 10.1016/j.cels.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent Inputs Enhance the Robustness of Biological Oscillators

Abstract: SUMMARY Robust biological oscillators retain the critical ability to function in the presence of environmental perturbations. Although central architectures that support robust oscillations have been extensively studied, networks containing the same core vary drastically in their potential to oscillate, and it remains elusive what peripheral modifications to the core contribute to this functional variation. Here, we have generated a complete atlas of two- and three-node oscillators computationally, then system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…The oscillation of protein levels and activities caused by feedback and feedforward systems constitutes a challenge when the cell cycle needs to be paused; it is not easy to freeze a complex free-running self-sustained oscillator [9]. Even if the oscillation is stopped, the system is likely to keep changing towards a new steady state.…”
Section: Introductionmentioning
confidence: 99%
“…The oscillation of protein levels and activities caused by feedback and feedforward systems constitutes a challenge when the cell cycle needs to be paused; it is not easy to freeze a complex free-running self-sustained oscillator [9]. Even if the oscillation is stopped, the system is likely to keep changing towards a new steady state.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting next step in bottom‐up synthetic biology is to reconstruct a cell cycle completely from scratch. Computational studies have shown that even with complicated biological clock networks, a minimal core architecture is sufficient for self‐sustained oscillations, while those evolutionary‐conserved peripheral network structures may provide additional modifications to promote functions such as robustness (Z. Li, Liu, & Yang, 2017) and tunability (Tsai et al, 2008). Indeed, a landmark study has successfully reconstituted a temperature‐compensated bacterial circadian clock in a test tube with components as simple as three Kai proteins and ATP (Nakajima et al, 2005), exemplifying a minimal design of a circadian clock.…”
Section: Scales In Time and Spacementioning
confidence: 99%
“…Besides adaptation, several studies have focused on understanding the emergence of functionalities such as oscillation, toggle switches, and determining the underlying circuitry [13][14][15][16], employing methods ranging from brute force searches [16] and rulebased modelling [13] to control-theoretic approaches [15]. Tyson et al (1974) conceived a two-protein negative feedback model with specific rate kinetics to prove the existence of an invariant Poincaré-Bendixson annulus which can lead to oscillation [13].…”
Section: Introductionmentioning
confidence: 99%